The Effect of Ageist Behaviors on Home Care Workers' Job Satisfaction and Retention in Long-Term Care. (February 2022) - Liu, Chien-Chih; Liu, Li-Fan; Chuang, Shuang-Shii
Objectives: This study aimed to examine how intrinsic and extrinsic factors of job satisfaction affect home care workers' intention to stay and determine whether ageist behaviors moderate the relation between job satisfaction and intention to stay. Method: We recruited 380 participants to complete measures of job satisfaction, ageist behaviors, and intention to stay. Results: Monthly wages, extrinsic and intrinsic factors, and positive and negative ageist behaviors were significantly related to home care workers' retention. Both positive and negative ageist behaviors negatively moderated the relation between job satisfaction and retention. Conclusion: Home care workers' retention may be increased by providing reasonable extrinsic rewards and enhancing the intrinsic nature of the job itself. Reducing negative ageist behaviors and increasing positive ones for those with low job satisfaction could be related to higher retention. The harmful effects of positive behaviors should be addressed. These findings could contribute to workforce retention in long-term care.